Saudi Arabia : 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that the rising oil prices and production resulted in large external and fiscal surpluses for Saudi Arabia. Real GDP growth is projected to slow to 2.8 percent in 2015, and then further to 2.4 percent in 2016 as government spending begins to adjust to the lower oil price environment. Nevertheless, government debt is very low and was 1.6 percent of GDP at end-2014. The current account surplus declined to 10.9 percent of GDP in 2014. It is expected to move into a small deficit in 2015 but return to surplus during 2016-20. Over the medium term, growth is expected to be about 3 percent. Inflation is likely to remain subdued.